2009
DOI: 10.1679/aohc.72.217
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule anatomy by atomic force microscopy and recognition imaging

Abstract: vinculin-actinin adaptor-interaction, we investigated their structural properties using the recognition mode of AFM. For this purpose, we attached an anti-Actinin-4 monoclonal antibody to the AFM cantilever and performed recognition imaging against Actinin-4. We finally succeeded in mapping the epitopic region within the Actinin-4 molecule. Thus, recognition imaging using an antibody coupled AFM cantilever will be useful for singlemolecule anatomy of biological macromolecules and structures. IntroductionAtomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…In a previous report in the same population, after adjusting for other confounding factors in the multivariable analysis narrower rim area was significantly associated with lower CSFP or higher TLCPD. Our findings are similar to the report that primary changes in CSFP or TLCPD are not likely to lead to laminar deformation or to produce a "glaucomatous" optic neuropathy in which the lamina deforms [23,[48][49][50][51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 90%
“…In a previous report in the same population, after adjusting for other confounding factors in the multivariable analysis narrower rim area was significantly associated with lower CSFP or higher TLCPD. Our findings are similar to the report that primary changes in CSFP or TLCPD are not likely to lead to laminar deformation or to produce a "glaucomatous" optic neuropathy in which the lamina deforms [23,[48][49][50][51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 90%
“…The ability of recognition imaging to characterize interactions between molecules of various shapes is one of its advantages over other single-molecule analytical techniques. Recognition imaging also enables the mapping of intra-molecular regions, such as the ligand-binding domain of α-actinin 4 (Takahashi et al, 2009). Using recognition imaging with synaptotagmin and SNAREs, we have shown that synaptotagmin can bind to both syntaxin 1A and the syntaxin 1A-SNAP-25 complex in the absence of Ca 2+ .…”
Section: +mentioning
confidence: 98%
“…AFM-FS (Stroh et al, 2004;Hinterdorfer and Dufrene 2006;Tang et al, 2007;Dufrene and Hinterdorfer 2008;Takahashi et al, 2009) is crucial due to its wide range of applications (Mayyas et al, 2010). Other than determining the binding kinetics and interaction forces, AFM-FS has also been utilized to understand the unfolding and folding of nucleic acids with multiple repeated units and single proteins, as well as to study molecule-material interface and molecule-molecule interactions.…”
Section: Understanding the Binding Dynamics Between The Targeted Receptor And Drug Delivery Vehiclementioning
confidence: 99%
“…All these modes will be described in more details in the following sections of this review paper. "Recognition AFM" or recognition imaging has facilitated usage of AFM (Stroh et al, 2004;Ebner et al, 2005;Hinterdorfer and Dufrene 2006;Tang et al, 2007;Dufrene and Hinterdorfer 2008;Takahashi et al, 2009;Chtcheglova and Hinterdorfer 2018;Koehler et al, 2019) as biosensor and enhanced its performance as a "characterization and detection tool" of biomolecules. A magnetic cantilever, stimulated by an external magnetic field, is oscillated in liquid in topography and recognition imaging (TREC) as shown in Figures 2A-B (Ebner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%